Aceticlastic and NaCl-Requiring Methanogen “Methanosaeta pelagica” sp. nov., Isolated from Marine Tidal Flat Sediment - Mori, Koji (American Society for Microbiology, 2012)
Among methanogens, only 2 genera, Methanosaeta and Methanosarcina, are known to contribute to methanogenesis from acetate, and Methanosaeta is a specialist that uses acetate specifically. However, Methanosaeta strains so far have mainly been isolated from anaerobic digesters, despite the fact that it is widespread, not only in anaerobic methanogenic reactors and freshwater environments, but also in marine environments, based upon extensive 16S rRNA gene-cloning analyses. In this study, we isolated an aceticlastic methanogen, designated strain 03d30q(T), from a tidal flat sediment. Phylogenetic analyses based on 16S rRNA and mcrA genes revealed that the isolate belongs to the genus Methanosaeta. Unlike the other known Methanosaeta species, this isolate grows at Na(+) concentrations of 0.20 to 0.80 M, with an optimum concentration of 0.28 M. Quantitative estimation using real-time PCR detected the 16S rRNA gene of the genus Methanosaeta in the marine sediment, and relative abundance ranged from 3.9% to 11.8% of the total archaeal 16S rRNA genes. In addition, the number of Methanosaeta organisms increased with increasing depth and was much higher than that of Methanosarcina organisms, suggesting that aceticlastic methanogens contribute to acetate metabolism to a greater extent than previously thought in marine environments, where sulfate-reducing acetate oxidation prevails. This is the first report on marine Methanosaeta species, and based on phylogenetic and characteristic studies, the name “Methanosaeta pelagica” sp. nov. is proposed for this novel species, with type strain 03d30q.